FIGURATIVE LANGUAGE IN “THE NIGHTINGALE AND THE ROSE” SHORT STORY BY OSCAR WILDE - Sutfi Ningsih, Darda (BASIS (Bahasa dan Sastra Inggris), 2025)
This study investigates students’ ability to identify and interpret figurative language in the old literature short story “The Nightingale and the Rose” by Oscar Wilde. Figurative language such as metaphor, simile, symbolism, personification, and hyperbole plays an essential role in conveying deeper meanings within literary works. However, students often face challenges in understanding these elements due to complex language structures and cultural contexts. This study employed a mixed-methods descriptive approach, combining qualitative interpretation of students’ analyses with quantitative coding to calculate the frequency of figurative language types. The participants were 17 sixth-semester English Department students at STKIP Muhammadiyah Sungai Penuh. Data were collected through guided literary analysis tasks. The findings revealed that students showed varied comprehension levels: metaphor (58.83%) and simile (52.94%) were the most accurately identified, while symbolism (23.52%) remained the most difficult. The study suggests that guided reading and literary discussion significantly enhance students’ interpretative skills. Effective teaching strategies are needed to help learners appreciate figurative language in old literature.